Jaipongan in the Dialectic of Tradition and Modernity - Yulaeliah, Ela; Saepudin, Asep (Proceeding of International Conference on Art, Media, and Culture (ICAMAC), 2024)
The emergence of modern thinkers in the realm of Sundanese tradition did not always go smoothly, but began with a gap on both sides, both at the level of understanding and in artistic practice. This article aims to describe the process of the gap between supporters of traditional music and modern thinkers, as well as the dialectical process that occurs when a change is made. The dialectical concept developed by Hegel regarding thesis, antithesis, and synthesis is used to uncover problems. Qualitative methods with a case study approach were used in this research. The material object analyzed is Jaipongan art. Data collection was carried out through observation, interviews, literature study, and documentation. The results show that there is a gap/contradiction between supporters of tradition and modern Jaipongan thinkers due to the lack of intense communication between the two parties when changes occur. The dialectical process that occurs between the two is carried out in several ways, including: through creativity, compromise, communication/interaction, and publications carried out by agents of change. This research concludes that dialogue/communication/interaction between adherents of tradition and modernity can essentially create a new culture as a dialectical result of the two. The two will be in harmony if each side has openness in understanding existences outside themselves that have different characters.